Recent progress on liquid metals and their applications - Bo, Guyue; Ren, Long; Xu, Xun; Du, Yi; Dou, Shixue (Advances in physics: X, 2018)
Gallium-based liquid metals show excellent thermal and electrical conductivities with low viscosity and non-toxicity. Their melting points are either lower than or close to room temperature, which endows them with additional advantages in comparison to the solid metals; for example, they are flexible, stretchable and reformable at room temperature. Recently, great improvements have been achieved in developing multifunctional devices by using Ga-based liquid metals, including actuators, flexible circuits, bio-devices and self-healing superconductors. Here, we review recent research progress on Gallium-based liquid metals, especially on the applications aspects. These applications are mainly based on the unique properties of liquid metals, including low melting point, flexible and stretchable mechanical properties, excellent electrical and thermal conductivities and biocompatibility.